Cultural Origin and Minority Shareholder Expropriation: Historical Evidence - GU, ZHIHUI; SUN, WEI; ZHOU, FRANK S. (Journal of Accounting Research, 2024)
ABSTRACT Can culture explain regional differences in minority shareholder expropriation? Examining regional variation in China, we document that the influence of historical Confucian values persists, despite decades of political movements clamping down on these values, and that these values reduce minority shareholder expropriation in local public firms. The effect on minority shareholder expropriation, in part, operates through the establishment of oversight mechanisms (i.e., greater financial reporting quality and dividend payouts) that constrain expropriation. The findings have important implications for understanding the origins of enduring regional differences in minority shareholder expropriation and capital market development.